A georeferenced database of the edaphic biota currently available for Argentina - Sanabria, María Cynthia Valeria (2023)
Background Soils have been studied and classified in terms of their physical and chemical characteristics, while the knowledge about biodiversity and the ecosystem processes that they support is lagging behind. Furthermore, the advance in scientific knowledge contributed by different researchers is dispersed and it is necessary to collect it to bring the big picture into focus. Today, it is possible to have the findings and data collected by different researchers, compile them and, based on technological advances, have tools that allow the information to be analysed in its entirety. The main objective of this work is to compile and systematise all the bibliographic information available on the main organisms that make up biodiversity in the soil: Acari, Collembola and Crassiclitellata in Argentina. This information will then allow us to link the composition and structure of the soil community with processes and flows in the ecosystem, and to estimate them at different scales and in soils with different anthropic impact. The database presented here gathers presence information on the mentioned taxa, their geographical location for the entire country, while preserving the identity and authorship of each scientific work retrieved. The taxonomic range of the organisms of the edaphic biota collected in this database ranges from class to subspecies and are registered, based on the taxonomic level reported by the original author in their research. The publications were obtained from Google Scholar, Scopus and JSTOR. In addition, records were added from INEDES theses, library searches, information requested from authors cited in other articles and unpublished works. In total, information was collected from 224 scientific publications, as well as personal information requested directly from some authors. The total number of registered individuals so far is 4838 of which 3049 specimens correspond to Acari, 944 to Classiclitellata and 845 belong to Collembola. New information This work is the first to gather, in a single publication, the entire dataset for all the Acari, Collembola and Clitellata recorded for Argentina.